Nitrate reductase-mediated synthesis of silver nanoparticles from AgNO3 - Kumar, S. Anil; Abyaneh, Majid Kazemian; Gosavi, S. W.; Kulkarni, Sulabha K.; Pasricha, Renu; Ahmad, Absar; Khan, Mohammad Islam (Biotechnology Letters, 2007)
Synthesis of silver nanoparticles using alpha-NADPH-dependent nitrate reductase and phytochelatin in vitro has been demonstrated for the first time. The silver ions were reduced in the presence of nitrate reductase, leading to the formation of a stable silver hydrosol 10-25 nm diam. and stabilized by the capping peptide. The nanoparticles were characterized by X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy and UV-Vis absorption. These studies will help in designing a rational enzymatic strategy for the synthesis of nanomaterials of different chemical composition, shapes and sizes as well as their separation.
Keywords: Capping Peptide; enzymatic method; nitrate reductase; silver nanoparticles

New route for preparation of luminescent mercaptoethanoate capped cadmium selenide quantum dots - Wankhede, Manoj E.; Inamdar, Shaukatali N.; Deshpande, Aparna; Thete, Aniket R.; Pasricha, Renu; Kulkarni, Sulabha K.; Harani, Santosh K. (Bulletin of Materials Science, 2008)
We report a synthesis of cadmium selenide quantum dots (Q-CdSe) by refluxing a mixture of cadmium acetate, selenium powder, sodium sulfite and 2-mercaptoethanol in N,N'-dimethyl formamide (DMF)/water solution. X-ray and electron diffractions suggest the formation of hexagonal phase of size quantized CdSe. Based on TEM analysis, the formation of nanoparticles with an average diameter of 3.5 +/- 0.5 nm is inferred. Their sols in DMF and dimethyl sulphoxide (DMSO) gave characteristic absorption peaks at 300 nm and 327 nm, which is attributed to the formation of high quality, size quantized CdSe particles. Extracted particles from the sol were readily redispersed in DMF and DMSO, which were diluted further with water without losing their optical and colloidal properties. FTIR spectroscopy suggested the formation of 2-mercaptoethanol thiolate on the particle surface, with free -OH groups available for linkage. Sols in DMSO and their solutions in water displayed an intense photoluminescence (PL).
Keywords: chalcogenides; Chemical synthesis; photoluminescence; semiconductor quantum dots